2011
DOI: 10.1186/1472-6920-11-91
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of team-based learning for undergraduate clinical neurology education

Abstract: BackgroundTeam-based learning (TBL), a new active learning method, has not been reported for neurology education. We aimed to determine if TBL was more effective than passive learning (PL) in improving knowledge outcomes in two key neurology topics - neurological localization and neurological emergencies.MethodsWe conducted a modified crossover study during a nine-week internal medicine posting involving 49 third-year medical undergraduates, using TBL as the active intervention, compared against self-reading a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 34 publications
7
74
0
10
Order By: Relevance
“…Moreover, Tan et al compared TBL with passive learning and reported that TBL is an effective technique for improving knowledge in undergraduate clinical neurology education. 20 In this study, the post-test scores were significantly higher than the pre-test scores. By working together in highly prepared and structured settings, the students performed better as a group.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, Tan et al compared TBL with passive learning and reported that TBL is an effective technique for improving knowledge in undergraduate clinical neurology education. 20 In this study, the post-test scores were significantly higher than the pre-test scores. By working together in highly prepared and structured settings, the students performed better as a group.…”
Section: Discussionmentioning
confidence: 84%
“…18,19 Educational experiences using the TBL format were also compared with other methods. 20,21 For example, Mody et al compared TBL with the lecture-based method and showed that TBL can be used as a novel approach for medical students' education in family planning. 2 This is in agreement with our work.…”
Section: Discussionmentioning
confidence: 99%
“…18 The authors reported that team-based learning provided improved knowledge for all students as compared with passive learning. There was, however, particular benefit to those students who were academically the weakest.…”
Section: Application Of Team-based Learning In Healthcare Education Mmentioning
confidence: 99%
“…In the foundational sciences, team-based learning has been used to teach medical students such varied topics as physiology, 15 pathology, 16 pharmacology, 17 neurology, 18 and anatomy. [19][20][21] Seidel and Richards reported that in addition to increased student engagement, there was an impressive level of student reasoning when teams were discussing physiology problems.…”
Section: Application Of Team-based Learning In Healthcare Education Mmentioning
confidence: 99%
“…The optional open-book component in TBL poses no negative effects in terms of decline in performance but rather an improvement in students' individual scores (Tan et al, 2011) as compared to conventionally described models of TBL. One study examining repeated testing by Marsh et al suggests that ease of recall can act to distract students into believing they understand the question and thus choose the incorrect answer upon retesting Puthucheary J, Goh S, Ha T, Graham D, Cook S MedEdPublish https://doi.org/10.15694/mep.2017.000072 (Marsh, Roediger, Bjork, & Bjork, 2007).…”
Section: Discussionmentioning
confidence: 99%